PENGARUH VARIASI KOMPOSISI BATANG, PELEPAH, DAN DAUN TANAMAN KELAPA SAWIT TERHADAP KUALITAS BRIKET BIOARANG - Edhi Sarwono; Muhammad Bayu Adinegoro; Budi Nining Widarti (Mulawarman University Press, 2018)
Abstract Search and development alternative energy sourced form nature should be done. Alternatif energy can be created through biomassa has sustained high value especially oil palm. East Borneo is one of foreign exchange contributor with oil palm plantation. BPS Kaltim recorded in 2013 oil palm production reach 6.902.602 ton form plant area 944.826 ha. Oil Palm plants elderly (aged above 20-25 years) has high trunk size. This matter reduce efficiency in the harvest oil palm so that oil palm cut down then replanting oil palm plants. Trunk, midrib. and leaf for waste oil palm plantation replanting, it has not been used optimally. This research purpose for utilize trunk, midrib and leaf oil palm as raw material production briquette bioarang as alternative fuel. This research use with 6 variation material that is, variation 1 (50% trunk : 10% midrib : 40% leaf), variation 2 (50% trunk : 20% midrib : 30% leaf), variation 3 (50% trunk : 30% midrib : 20% leaf), variation 4 (100% trunk : 0% midrib : 0% leaf), variation 5 (0% trunk : 100% midrib : 0% leaf), dan variation 6 (0% trunk : 0% midrib : 100% leaf). Material be prepared then Carbonizaion (pyrolisis) process to produce rendmenen and tar. Rendemen mashed, mixed with adhesive tapioka, and formed become briquette bioarang. Test analysis moisture, ash, volatile matter, fixed carbon dan calorific value for knowing briquette bioarang quality. Result for the analysis is optimum composition briquette bioarang in variation 5 (0% trunk : 100% midrib : 0% leaf) with average value moisture 0,1958%, ash 13,0542%, volatile matter 49,3947%, fixed carbon 37,3553%, and calorific value 5419,53 cal/gr. Rendemen trunk 26,67%, midrib 58,33%, and leaf 50%. Tar variation 1 (50% B : 10% P : 40% D) 100 ml, variation 2 (50% B : 20% P : 30% D) 150 ml, dan variation 3 (50% B : 30% P : 20% D) 210 ml. Keyword: Fuel, Oil Palm, Briquette Bioarang.